Convergence Analysis of Rust Fungi and Anther Smuts Reveals Their Common Molecular Adaptation to a Phytoparasitic Lifestyle - Zhou, Xianzhen; Yu, Dan; Cao, Zhimin (Frontiers in Genetics, 2022)
Convergent evolution between distantly related taxa often mirrors adaptation to similar environments. Rust fungi and anther smuts, which belong to different classes in Pucciniomycotina, have independently evolved a phytoparasitic lifestyle, representing an example of convergent evolution in the fungal kingdom. To investigate their adaptations and the genetic bases underlying their phytoparasitic lifestyles, we performed genome-wide convergence analysis of amino acid substitutions, evolutionary rates, and gene gains and losses. Convergent substitutions were detected in ATPeV0D and RP-S27Ae, two genes important for the generation of turgor pressure and ribosomal biosynthesis, respectively. A total of 51 positively selected genes were identified, including eight genes associated with translation and three genes related to the secretion pathway. In addition, rust fungi and anther smuts contained more proteins associated with oligopeptide transporters and vacuolar proteases than did other fungi. For rust fungi and anther smuts, these forms of convergence suggest four adaptive mechanisms for a phytoparasitic lifestyle: (i) reducing the metabolic demand for hyphal growth and penetration at the pre-penetration stage, (ii) maintaining the efficiency of protein synthesis during colonization, (iii) ensuring the normal secretion of rapidly evolving secreted proteins and (iv) improving the capacity for oligopeptide metabolism. Our results shed the first light on the genetic convergence mechanisms and molecular adaptation underlying phytoparasitic lifestyles in fungi.